2017
DOI: 10.1590/1414-431x20175868
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept protects rat cardiomyocytes against hypertrophy by regulating inflammatory cytokines secretion and cell apoptosis

Abstract: We aimed to investigate the effect of etanercept, a tumor necrosis factor-a (TNF-a) inhibitor, on rat cardiomyocyte hypertrophy and its underlying mechanism. Primary neonatal rat cardiomyocytes were isolated from Sprague-Dawley rats. The model of rat cardiomyocyte hypertrophy was induced by endothelin, and then treated with different concentrations of etanercept (1, 10, and 50 mM). After treatment, cell counts, viability and cell apoptosis were evaluated. The mRNA levels of myocardial hypertrophy marker genes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The effects of these drugs on myocardial remodeling and diastolic dysfunction have been contradictory (Kosmas et al, 2019). Some have shown that blocking circulating inflammatory cytokines positively impacts the cellular mechanisms implicated in myocardial remodeling (Kleveland et al, 2016; Li et al, 2017), while others have failed to show positive outcomes (Hartman et al, 2016). Nevertheless, the beneficial effects were shown in systems that did not involve chronic inflammation (Kleveland et al, 2016; Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of these drugs on myocardial remodeling and diastolic dysfunction have been contradictory (Kosmas et al, 2019). Some have shown that blocking circulating inflammatory cytokines positively impacts the cellular mechanisms implicated in myocardial remodeling (Kleveland et al, 2016; Li et al, 2017), while others have failed to show positive outcomes (Hartman et al, 2016). Nevertheless, the beneficial effects were shown in systems that did not involve chronic inflammation (Kleveland et al, 2016; Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some have shown that blocking circulating inflammatory cytokines positively impacts the cellular mechanisms implicated in myocardial remodeling (Kleveland et al, 2016; Li et al, 2017), while others have failed to show positive outcomes (Hartman et al, 2016). Nevertheless, the beneficial effects were shown in systems that did not involve chronic inflammation (Kleveland et al, 2016; Li et al, 2017). We have recently shown that systemic inflammation‐induced concentric remodeling, diastolic dysfunction (Le Roux et al, 2021; Mokotedi et al, 2020), and increased collagen area fraction (Mokotedi et al, 2020) in the collagen‐induced arthritis (CIA) rat model.…”
Section: Introductionmentioning
confidence: 99%
“…In human cardiac tissues under ischemic injury local production of TNF coupled with hypoxia-mediated induction of TNFR2 facilitate the transient proliferation and eventually differentiation of resident cardiac stem cells into mature cardiac myocytes [ 106 ]. Contrary to this in various models of experimental cardiac hypertrophy, TNF inhibitor was able to reduce heart hypertrophy, which was believed to be mediated by a reduction of levels of myocardial hypertrophy marker genes, including atrial natriuretic factor (ANF), matrix metalloproteinase (MMP)-9, and MMP-13 [ 107 ]. It is plausible that in these models TNF inhibitors blocks TNF signaling mediated by TNFR1 [ 108 ].…”
Section: The Role Of Tnf In Rheumatoid Arthritis and Heart Failurementioning
confidence: 99%
“…A liver X receptor agonist (TO901317) inhibits oxLDL-induced mitogenic effects of CT-1 [94]. Etanercept, a TNF-α inhibitor, decreases CT-1 levels secreted from neonatal rat cardiomyocytes [95]. These interventions against CT-1 may provide therapeutic advances for atherosclerotic cardiovascular diseases.…”
Section: Pharmacological Intervention Against Ct-1mentioning
confidence: 99%